2011
DOI: 10.1098/rsbl.2010.1145
|View full text |Cite
|
Sign up to set email alerts
|

Directional preference may enhance hunting accuracy in foraging foxes

Abstract: Red foxes hunting small animals show a specific behaviour known as 'mousing'. The fox jumps high, so that it surprises its prey from above. Hearing seems to be the primary sense for precise prey location in high vegetation or under snow where it cannot be detected with visual cues. A fox preparing for the jump displays a high degree of auditory attention. Foxes on the prowl tend to direct their jumps in a roughly north-eastern compass direction. When foxes are hunting in high vegetation and under snow cover, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 15 publications
2
44
0
Order By: Relevance
“…The north-northeast alignment of mousing behavior is consistent with SMA responses exhibited by a variety of terrestrial vertebrates [16]. Interestingly, when a direct view of the prey was obstructed by high vegetation or snow cover, foxes more accurately aligned their attacks to the north-northeast and were approximately 3-4 times more successful at capturing prey than when aligned in other magnetic directions [27]. The authors proposed that the alignment behavior observed in foxes could be mediated by a light-dependent magnetoreception mechanism, similar to that used by migratory birds, newts, and insects [7,14,[28][29][30][31][32][33] where specialized photopigments undergo a photo-induced chemical reaction that is sensitive to the alignment of the magnetic field.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…The north-northeast alignment of mousing behavior is consistent with SMA responses exhibited by a variety of terrestrial vertebrates [16]. Interestingly, when a direct view of the prey was obstructed by high vegetation or snow cover, foxes more accurately aligned their attacks to the north-northeast and were approximately 3-4 times more successful at capturing prey than when aligned in other magnetic directions [27]. The authors proposed that the alignment behavior observed in foxes could be mediated by a light-dependent magnetoreception mechanism, similar to that used by migratory birds, newts, and insects [7,14,[28][29][30][31][32][33] where specialized photopigments undergo a photo-induced chemical reaction that is sensitive to the alignment of the magnetic field.…”
Section: Introductionsupporting
confidence: 54%
“…Visual observations of 'mousing' red foxes, in which a fox is attracted to the sounds produced by small rodents and then performs an arching leap ('mousing') to land on the prey from above, showed a strong tendency for mousing attacks to be directed toward magnetic north-northeast [27]. The north-northeast alignment of mousing behavior is consistent with SMA responses exhibited by a variety of terrestrial vertebrates [16].…”
Section: Introductionmentioning
confidence: 48%
See 2 more Smart Citations
“…Annual captures in the Czech Republic currently range between 60 000 -80 000, and populations continue to grow (Placata, 2011). The increase in the distribution and density of the red fox in most European countries could be explained by a mortality rate reduction, which is due to an intensive campaigns of vaccination against rabies (oral baits) as well as to the opportunist behaviour of this species (Hanosset et al, 2008;Červený et al, 2004). The red fox is a common host of several dangerous zoonotic parasites, primarily the tapeworm Echinococcus multilocularis, causative agent of alveolar echinococcosis, a parasitic disease that causes a severe hepatic disorder in humans .…”
Section: Introductionmentioning
confidence: 99%